DNMT1 and HDAC2 Cooperate to Facilitate Aberrant Promoter Methylation in Inorganic Phosphate-Induced Endothelial-Mesenchymal Transition. - Xiaoying Tan; Xingbo Xu; Michael Zeisberg; Elisabeth M Zeisberg (PLoS ONE, 2016)
While phosphorus in the form of inorganic or organic phosphate is critically involved in most cellular functions, high plasma levels of inorganic phosphate levels have emerged as independent risk factor for cardiac fibrosis, cardiovascular morbidity and decreased life-expectancy. While the link of high phosphate and cardiovascular disease is commonly explained by direct cellular effects of phospho-regulatory hormones, we here explored the possibility of inorganic phosphate directly eliciting biological responses in cells. We demonstrate that human coronary endothelial cells (HCAEC) undergo an endothelial-mesenchymal transition (EndMT) when exposed to high phosphate. We further demonstrate that such EndMT is initiated by recruitment of aberrantly phosphorylated DNMT1 to the RASAL1 CpG island promoter by HDAC2, causing aberrant promoter methylation and transcriptional suppression, ultimately leading to increased Ras-GTP activity and activation of common EndMT regulators Twist and Snail. Our studies provide a novel aspect for known adverse effects of high phosphate levels, as eukaryotic cells are commonly believed to have lost phosphate-sensing mechanisms of prokaryotes during evolution, rendering them insensitive to extracellular inorganic orthophosphate. In addition, our studies provide novel insights into the mechanisms underlying specific targeting of select genes in context of fibrogenesis.